Estrategia psicopedagógica para el desarrollo de la interacción social en un niño con trastorno del espectro autista (tea) - Puente Plua , Bremhy Milena (2025)
Autism Spectrum Disorder (ASD) is a neurodevelopmental disorder that affects communication, social interaction, and behavior, presenting significant challenges in the integration of children with ASD into various contexts, especially in educational and family settings. This study aimed to design a psychopedagogical strategy to promote the development of social interaction in a child with ASD, fostering their integration into an inclusive environment. The methodology used was qualitative, based on a single case study, including interviews with teachers and family members, as well as direct observations in both the classroom and at home. Through an open and selective coding process, emerging categories were identified, reflecting the child’s main difficulties in social interaction, such as their tendency to isolate and struggles to follow social and emotional norms. The intervention involved applying structured activities designed to improve emotional self-regulation, encourage empathy, and enhance assertive communication. The results showed that the implementation of the psychopedagogical strategy led to significant improvement in the child’s ability to interact with peers at school and with family members at home. Furthermore, the active collaboration between teachers and parents was essential for the success of the intervention. In conclusion, the design of personalized strategies, focused on the emotional and social needs of children with ASD, is key to improving their social integration, contributing to their well-being and the development of healthy interpersonal relationships.